Avaliação da restrição alimentar quantitativa em parâmetros de desempenho e qualidade de carne de fêmeas f1 dorper x Santa Inês - Pereira, Fernando Felipe da Silva (2023)
The objective of this study was to evaluate different levels of feed restriction (ad libitum, 300 and 600 g/kg dry matter; DM) of performance, carcass traits, cut yield and meat quality of F1 Dorper x Santa Ines lambs. Twenty-four ewe lambs, F1 Dorper x Santa Ines with initial body weights (BW) of 19.5 ± 1.52 kg and four months old were distributed in a completely randomized design with three levels of feed restriction (ad libitum, 300 and 600 g/kg DM). The experimental trial lasted 135 days. Feed restriction linearly decreased (P<0.001) intakes of dry matter, organic matter, crude protein, ether extract, neutral detergent fiber corrected for ash and protein, non-fibrous carbohydrates, total carbohydrates, and total digestible nutrients. The digestibility of DM, OM, CP, EE, NDFap and TC were higher (P<0.05) in animals feed 600 g/kg DM restriction. Final BW decreased linearly (P<0.001) from 37.55 to 21.35 kg with feed restriction increasing. Cold carcass yield, subcutaneous fat thickness and rib eye area linearly decreased (P<0.05) with increasing feed restriction. The morphometric measurements (back width and internal length of carcass) linearly reduced (P<0.05) with increasing feed restriction, except for ham length (P>0.05). The leg weight linearly reduced (P<0.05) by levels of feed restriction. The commercial cuts of loin, shoulder, rib, lower rib, neck linearly reduced (P<0.05) with increasing feed restriction. The meat from animals fed at a feed restriction level of 600 g/kg DM showed higher moisture. The concentration of crude protein and fat in meat linearly decreased (P<0.05) with increasing dietary restriction. In conclusion, feed restriction decreases intake, performance and carcass traits; however, it improves nutrient digestibility.